Numerical simulation of wind characteristics at bridge site considering thermal effects. Issue 9 (July 2018) - Zhang, Mingjin; Li, Yongle; Wang, Bin; Ren, Sen
In order to study the variation of wind field characteristics under the influence of thermal effects at a bridge site in a deep-cutting gorge with high-altitude and temperature difference, the simulation of natural convection was realized by adding momentum source terms in FLUENT. And the correctness of the simulation results was verified. Then, choosing Dadu River Bridge located at a deep-cutting gorge in western Sichuan as an engineering background, combined with the variation of temperature tested at the bridge site, the numerical simulation of the wind field characteristics at the bridge site was carried out under the influence of the thermal effects. The influences of different thermal factors on the surface wind characteristics of bridge site area were discussed. The wind characteristics at the bridge site under the combined action of different wind velocities and thermal effects were analyzed. As shown in the results, the maximum vertical wind velocity caused by the thermal effects at the height of main girder is 3.0 m/s, and the maximum horizontal wind velocity is 6.4 m/s. When the upcoming wind velocity is greater than 5.0 m/s, the thermal effects have been significantly reduced, and the wind field at the bridge site is mainly influenced by the upcoming wind velocity, wind direction, and local terrain. Under the influence of thermal, the surface temperature distribution at the bridge site is significantly uneven, which are obviously different from the case of not considering the thermal effects.